2010
DOI: 10.1186/1471-2350-11-27
|View full text |Cite
|
Sign up to set email alerts
|

Health status in patients at risk of inherited arrhythmias and sudden unexpected death compared to the general population

Abstract: BackgroundThe possibilities in the molecular genetics of long QT syndrome (LQTS) and hypertrophic cardiomyopathy (HCM) has made family screening, with diagnostic and predictive genetic testing part of the health care offer in genetic counselling of inherited arrhythmias, potentially affecting the subjective health among these individuals. The study compared health status among patients at risk of arrhythmia because of family history or clinical diagnosis of LQTS and HCM with reference health status scores of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
32
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(36 citation statements)
references
References 33 publications
3
32
1
Order By: Relevance
“…The psychological implications of having an ICD have been well studied, yet its effects on quality of life, anxiety, and depression are conflicting. 10,11 One small study suggested that quality of life and depression were worse in ICD patients with inherited diseases compared with those with ischemic or valvular heart disease. 12 The influence of appropriate or inappropriate shocks on quality-of-life measures, as assessed as a secondary end point in randomized trials, as well as smaller observational studies, is mixed and does not consistently support a negative association or relationship between number of shocks and psychological effects.…”
Section: Health-related Psychological Issues In Affected Individualsmentioning
confidence: 99%
See 1 more Smart Citation
“…The psychological implications of having an ICD have been well studied, yet its effects on quality of life, anxiety, and depression are conflicting. 10,11 One small study suggested that quality of life and depression were worse in ICD patients with inherited diseases compared with those with ischemic or valvular heart disease. 12 The influence of appropriate or inappropriate shocks on quality-of-life measures, as assessed as a secondary end point in randomized trials, as well as smaller observational studies, is mixed and does not consistently support a negative association or relationship between number of shocks and psychological effects.…”
Section: Health-related Psychological Issues In Affected Individualsmentioning
confidence: 99%
“…11 How might predictive genetic testing influence health perception? Individuals who test negative for a pathogenic familial mutation can be reassured that they and their offspring are no more at risk of developing that particular disease than the general population and can forego further clinical screening.…”
Section: Unaffected At-risk Individuals and Predictive Testingmentioning
confidence: 99%
“…Studies on these disorders have consistently shown impairments in health status and quality of life, with an elevated risk for anxiety and depression. [1][2][3][4] An implantable cardioverter defibrillator (ICD) may be indicated for primary or secondary prevention of SCD in these patients, and is likely to exacerbate psychological distress. Independent of underlying diagnosis, patients requiring ICDs commonly experience anxiety and/or depression related to the anticipation of a potential shock.…”
mentioning
confidence: 99%
“…However, the HCM group showed a ** Fig. 2 Health status, anxiety and depression of NCCM and dilated cardiomyopathy patients stratified by NYHA classification significantly lower general health, physical functioning, role physical, vitally and role emotional significantly lower compared to general population (and LQTS group) [25,26]. A few other studies reported almost no increase in prevalence of anxiety and depression in patients with inherited cardiac disease [27][28][29].…”
Section: Discussionmentioning
confidence: 94%